A Study on Demographic Status of Ksheena Shukra (Oligozoospermia) in Male Patients. - Jaiman, Devesh; Meena, H M L; Padhar, Bharat Kumar; Mutha, Rashmi; Rawat, Sunita; Rajpurohit, Ranweer Singh; Sharma, Parveen (International Research Journal of Ayurveda & Yoga, 2022)
Oligozoospermia contributes as the major factor of male infertility. Day by day drastic changes in activities like life style, sexual life, food habits, industrial and occupational hazards, environmental pollution have contributed to the increased incidence of Oligozoospermia. According to Ayurvedic classics, Oligozoospermia can be correlated with Ksheena Shukra. It was reported that 40 % of infertility cases related to men, 40 % related to women and 20 % related to both of sex. A male factor is present in the one half of infertile couples. The study was conducted on 60 diagnosed & confirmed patients of Oligozoospermia from OPD & IPD of NIA, Hospital, Jaipur. Maximum 56.67 % patients belonged to the age group of 21-35 years, 88.33 % patients were Hindu. 80 % of patients were married. 100 % of the patients had masturbation habit. 76.67% of the patients had masturbation habit before marriage. Maximum 40 % of the patient were having psychological factor like stress. 65 % of the patients reported to have moderate oligozoospermia i.e 6- 10 million/ml. 85 % of the patients had primary infertility and 85 % of the patients had Shrama Maithuna (Exertion during intercourse).